Rules for border-crossing factor movements - Horst Siebert (Kiel Institute for the World Economy (IfW), 2007)
This paper analyzes rules for international factor movements, i.e. real capital flows together with the relocation of firms, the flow of technology and the migration of people. These rules have to make sure that individuals, individual countries as well as the world economy benefit from factor flows. They also define whether factors are accumulated, for instance whether new technology is found. Except for TRIMS, an international investment code has not been established. Conventions have been introduced to ease patent applications. TRIPS protects intellectual property. Rules for labor migration relate to the right of exit and to conditions of entry. Factor movements are interdependent among themselves and with trade. This implies a pecking order between trade, capital flows and migration.
Keywords: F2; K; O3; P; 330; Capital flows; Technology; Patents; Intellectual property rights; Migration; Institutional arrangements; International rules; Internationale Faktormobilität; Internationale Handelspolitik; Welt